2011
DOI: 10.5762/kais.2011.12.5.2439
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption/Desorption Properties of VOCs on Activated Carbon Fiber

Abstract: We investigated the adsorption/desorption property of volatile organic compounds(VOC) by using activated carbon fibers(ACF) instead of activated carbon(AC) which is conventionally used. The adsorption behavior of the fixed bed and the breakthrough characteristics were also studied. As a result, ACFj showed 1.15 times higher adsorption amount as compared to AC. The breakthrough Point and adsorption amount of VOCs were decreased with the increase of temperature. In the case of AC, desorption time having 99% remo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…Baek et al [6] and Kim and Chang [7] also reported that the cm 3 /g, respectively. Therefore, the specific surface areas of the two ACFs were 1690 m 2 /g and 1090 m 2 /g, respectively.…”
Section: Toluene Adsorption Capacity Of Different Types Of Acfsmentioning
confidence: 90%
See 2 more Smart Citations
“…Baek et al [6] and Kim and Chang [7] also reported that the cm 3 /g, respectively. Therefore, the specific surface areas of the two ACFs were 1690 m 2 /g and 1090 m 2 /g, respectively.…”
Section: Toluene Adsorption Capacity Of Different Types Of Acfsmentioning
confidence: 90%
“…Such an explanation is equivalent to the study of Dubinin [14], Huang et al [15] and others. Baek et al [6] reported that it was possible to obtain a maximum adsorption capacity of 370 mg/g-acf when passing toluene vapor of 100 ppm at 0.5 L/min through an 0.03 g ACF packed bed. This was approximately twice that in this experiment, thereby displaying a substantially better adsorption capacity of toluene.…”
Section: Toluene Adsorption Capacity Of Different Types Of Acfsmentioning
confidence: 99%
See 1 more Smart Citation